Studi Kelayakan Investasi Perumahan Menggunakan Metode Benefit Cost Ratio - Imam Sururi; Hammam Rofiqi Agustapraja (Jurnal Teknik, 2020)
Investment is the association of a financial source in a long period to generate profits in the future/future. Housing is a group of houses that are either narrow or broad that functions as a residential or residential environment for the people who occupy it. The problem statement is to find out whether the house type 30/60 in the Lamongan Regency Insani housing is worth investing in when viewed from a financial perspective. The purpose of this study was to determine the feasibility of Insani Regency Lamongan housing investment. The method used to analyze the investment feasibility is the Benefit-Cost Ratio. Based on the results of this research, the Lamongan Regency Insani Housing showed that it was feasible because it produced a Benefit-Cost Ratio of 1,307.